Lizards on the mantel, burros at the door : a Big Bend memoir - Koch, Etta, 1904- (University of Texas Press, 1999)
Etta Koch and her daughter June Cooper Price chronicle their family's first years (1944-1946) in the Big Bend. Based on authentic journals and letters.